Nyeri persalinan dan tingkat kecemasan pada ibu inpartu kala I fase aktif - Sunarsih Sunarsih; Tuti Puspita Sari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Labor pain and anxiety levels in the mothers inpartu active phase of the first stage at Metro medical center, Lampung-IndonesiaBackground: Anxious feeling whom mother felt at give birth process would influence toward painful sensation in giving a birth. The presurvey result that done at Metro medical center, finding of 7 mother who give birth, most of them (71,4 %) had anxious level that was medium, and there were of 4 mother (57, 2%) had a light pain, and of 3 was a medium pain.Purpose: Knowing the correlation of labor pain and anxiety levels in the mothers inpartu active phase of the first stageatmedical center, Metro Lampung-IndonesiaMethod: A quantitative with cross sectional and the sample of 31 inpartu active phase by using accidentall sampling method. Instrument for painful intensity used Baurbanispainful scale and for anxious level’s by using State-trait anxiety inventory (STAI) Form Y-1. This research had done on2018 and data analyses used person product moment test.Results: Finding that the average of anxious level inpartu mother was of 51.35 and the average of pain score was of 4,68.Conclusion: There was correlation between of labor pain and anxiety levels in the mothers inpartu active phase of the first stage at medical center, Metro Lampung-Indonesia. Medical care provider to be give more information regarding the birth physiology in order to mother could prevent anxious feeling during giving birth process.Keywords: Labor Pain; Anxiety Levels; Mothers InpartuPendahuluan: Rasa cemas yang dialami ibu pada proses persalinan akan berpengaruh terhadap nyeri pada persalinan. Hasil prasurvey yang dilakukan di BPS P Kota Metro menunjukkan bahwa dari 7 ibu bersalin, sebagain besar (71,4%) memiliki tingkat kecemasan sedang dan sebanyak 4 ibu bersalin (57,2%) memiliki intensitas ringan, 3 ibu (42,8%) memiliki intensitas nyeri sedang.Tujuan: Diketahuinya hubungan tingkat kecemasan terhadap nyeri pada ibu inpartu kala I fase aktif di BPS P Kota Metro.Metode:Penelitian kuantitatif, dengan desain penelitian cross sectional dan sampel berjumlah 31. Pengambilan sampel dengan metode accidental sampling. Pengumpulan data intensitas nyeri menggunakan skala nyeri Bourbanis, sedangkan pengumpulan data tingkat kecemasan ibu bersalin dilakukan menggunakan State-trait anxiety inventory (STAI) Form Y-1. Penelitian telah dilaksanakan pada tahun 2018. Analisa data menggunakan uji person product moment. Hasil: Diperoleh rata-rata tingkat kecemasan ibu inpartu adalah 51,35 dan rata-rata skor nyeri yang dirasakan adalah 4,68.Simpulan: Adanya hubungan antara tingkat kecemasan dengan nyeri ibu inpartu kala I fase aktif. Bagi ibu yang akan menjalani proses persalinan hendaknya menggali informasi tentang fisiologis persalinan agar ibu bersalin mampu mencegah terjadinya kecemasan selama proses persalinan.